Federal reserve communications and newswire coverage - Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
In this paper, we explore the determinants of media coverage of Federal Reserve (Fed) communications. Our sample covers all 344 forward-looking communications made in the period May 1999-May 2004. We find, first, that there is a higher likelihood of media coverage for monetary policy reports and speeches by Greenspan than for testimony and speeches by other Fed members. Furthermore, communications with an explicit monetary policy inclination or tone different from the current interest rate path are particularly likely to be covered. However, the release of important macroeconomic news reduces the likelihood of media coverage. Second, speeches by regional Fed presidents are relatively less likely to be reported than speeches by Board members. Nevertheless, media coverage of Fed president speeches is more likely if central bank communication is stale. Finally, our results indicate that Ben Bernanke played a distinguished role even before his chairmanship.
Keywords: D83; E52; E58; 330; Central Bank Communication; Federal Open Market Committee; Federal Reserve; Newswire Coverage; Monetary Policy